2013
DOI: 10.2217/pme.13.17
|View full text |Cite
|
Sign up to set email alerts
|

A National Study of Breast and Colorectal Cancer Patients‘ Decision-Making for Novel Personalized Medicine Genomic Diagnostics

Abstract: This study provides insights into the relative weight that breast and colorectal cancer patients place on various aspects of molecular genomic diagnostics, and the trade-offs they are willing to make among attributes of such tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…It is possible that the findings may not be generalizable to all HCPs and consumers in oncology as there is evidence that differences exist in the knowledge and practices across different subspecialities, professions, and work settings. 26,29,35 In line with previous studies in noncancer-specific settings, 15,[43][44][45] the results of this systematic review reinforce the notion that utility of PGx testing in oncology is perceived positively by both HCPs and patients. Costs and lack of insurance coverage were found to be the main barriers in adoption of PGx testing in oncology.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is possible that the findings may not be generalizable to all HCPs and consumers in oncology as there is evidence that differences exist in the knowledge and practices across different subspecialities, professions, and work settings. 26,29,35 In line with previous studies in noncancer-specific settings, 15,[43][44][45] the results of this systematic review reinforce the notion that utility of PGx testing in oncology is perceived positively by both HCPs and patients. Costs and lack of insurance coverage were found to be the main barriers in adoption of PGx testing in oncology.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, both HCPs and consumers perceived PGx in oncology positively, in particular the potential of PGx in guiding cancer treatment to improve efficacy and minimize toxicity. [19][20][21][22][23][24][26][27][28][29][30]32,35,37,[39][40][41] It was found that there is a high level of acceptance of PGx testing (~90% across studies) and information among consumers, including those who had PGx testing and those who had not had PGx testing and were asked hypothetical questions about PGx, [19][20][21][27][28][29]32,40 and two studies reported that patients with cancer expressed high willingness to pay for PGx tests. 21,29 Two studies, Dodson and Przybylski et al, 23,38 assessed the prior PGx education HCPs had received and found that most had no formalized PGx education during their undergraduate training.…”
Section: Summary Of Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two interviewees pointed out that in the case of a screening program aimed at asymptomatic women, the effect of breast cancer genetic test results in underwriting is more problematic because some women—even at low risk—may never develop the disease and yet may still be perceived to be at higher risk than the average population by insurers. Such concerns about insurers' interest in genetic data have been reported in other studies where patients have been reluctant or refused to undergo breast cancer genetic testing or, expressed a preference for paying higher out-of-pocket costs if doing so could potentially prevent insurers from having access to their test results (Armstrong et al, 2003 , p. 28; Issa et al, 2013 , p. 253).…”
Section: Discussionmentioning
confidence: 85%
“…It encompasses a variety of tools and interventions such as computerized alerts and reminders, clinical guidelines, order sets, patient data reports and dashboards, documentation templates, diagnostic support, and clinical workflow tools" [39]. It has been shown that in decision-making about genomic diagnostics, cancer patients place a high value on physician recommendations and interpretation of the results [40]. Physicians' adoption and use of pharmacogenomic and other genomic-based data have been proven to be dependent upon ease of use including interpretation of the genomic testing results [41].…”
Section: The Critical Role Of Clinical Decision Supportmentioning
confidence: 99%